The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3847/2041-8213/acaeac
|View full text |Cite
|
Sign up to set email alerts
|

PHANGS–JWST First Results: The Dust Filament Network of NGC 628 and Its Relation to Star Formation Activity

Abstract: PHANGS–JWST mid-infrared (MIR) imaging of nearby spiral galaxies has revealed ubiquitous filaments of dust emission in intricate detail. We present a pilot study to systematically map the dust filament network (DFN) at multiple scales between 25 and 400 pc in NGC 628. MIRI images at 7.7, 10, 11.3, and 21 μm of NGC 628 are used to generate maps of the filaments in emission, while PHANGS–HST B-band imaging yields maps of dust attenuation features. We quantify the correspondence between filaments traced by MIR th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 86 publications
2
17
0
Order By: Relevance
“…In the 21 μm map, this removes large-scale emission (constituting ∼50% of the total emission) originating from the interstellar radiation field, which is not related to recent massive star formation but has a nonnegligible contribution to the dust heating (Draine & Li 2007;Verley et al 2009). Thilker et al (2023) report a fraction of mid-infrared emission arising from filamentary structures (∼30%) that is qualitatively similar to the ∼50% obtained here. The fraction of large-scale emission removed is also broadly consistent with the contribution of the interstellar radiation field to Spitzer 24 μm wavelength measured in the Milky Way and in Local Group galaxies (20%-85%; Koepferl et al 2015;Viaene et al 2017;Williams et al 2019).…”
Section: Methodssupporting
confidence: 85%
See 1 more Smart Citation
“…In the 21 μm map, this removes large-scale emission (constituting ∼50% of the total emission) originating from the interstellar radiation field, which is not related to recent massive star formation but has a nonnegligible contribution to the dust heating (Draine & Li 2007;Verley et al 2009). Thilker et al (2023) report a fraction of mid-infrared emission arising from filamentary structures (∼30%) that is qualitatively similar to the ∼50% obtained here. The fraction of large-scale emission removed is also broadly consistent with the contribution of the interstellar radiation field to Spitzer 24 μm wavelength measured in the Milky Way and in Local Group galaxies (20%-85%; Koepferl et al 2015;Viaene et al 2017;Williams et al 2019).…”
Section: Methodssupporting
confidence: 85%
“…This data was obtained from the Mikulski Archive for Space Telescopes (MAST) at the Space Telescope Science Institute. 35 This mid-infrared wavelength has been widely used as a tracer of embedded star formation, because a substantial fraction of the emission, especially that with compact morphology, originates from dust excitation by radiation from surrounding massive stars and empirically exhibits a correlation with tracers of massive star formation (Kennicutt & Evans 2012;Galliano et al 2018;Hassani et al 2022;Leroy et al 2022;Thilker et al 2023). In particular, using four initial targets, Hassani et al (2022) have found that 90% of compact 21 μm sources are associated with H II regions detected in extinction corrected Hα maps from MUSE.…”
Section: Observationsmentioning
confidence: 99%
“…In addition, the 3.3 μm feature can be mapped with NIRCam at 2-3 times finer angular resolution than the 7.7 μm or 11.3 μm bands, yielding 5-10 pc resolution in our targets. This allows measurements of the sizes of H II regions and bubbles (see Barnes et al 2023;Watkins et al 2023), the identification of filamentary structure (Meidt et al 2023;Thilker et al 2023), the identification of embedded clusters (Rodriguez et al 2023), and potentially tracing the gas column at higher resolution than is routinely possible with any millimeter or radio facilities (Leroy et al 2023;Sandstrom et al 2023).…”
Section: Discussionmentioning
confidence: 99%
“…MIR bands, such as the Mid-Infrared Instrument's (MIRI) F770W, trace hot dust heated by young stars and polycyclic aromatic hydrocarbons (PAHs), where PAHs are vibrationally excited in the presence of starlight (Sandstrom et al 2023), especially when illuminated by UV photons. Therefore MIR observations allow us to identify new, young embedded clusters obscured at optical wavelengths (Rodriguez et al 2023), large-scale filamentary structures containing dense, cold gas expected to host future star formation (Thilker et al 2023), and hot dust emission shining in the presence of UV radiation emitted by OB stars (Leroy et al 2023). Piecing these results together provides the observations needed to trace recent star formation histories within these galaxies (Kim et al 2023).…”
Section: Introductionmentioning
confidence: 98%